Franck Condon analysis of emission and excitation spectra of fused silica materials - Guesmi Mariem; Thor Tomas; Taboubi Oumayma; Šeděnková Ivana; Panthi Yadu Ram; Pfleger Jiri; Zidek Karel (EPJ Web of Conferences, 2023)
Analysis of defects in optical materials is essential for their applicability in cutting-edge optical components. Since fused silica (FS) counts among the most used materials, deep knowledge about the defects in FS is of high importance. These defects have been routinely identified by studying photoluminescence (PL) emission and its analysis via multiple Gaussian bands. Here we present an extended approach based on the Franck-Condon model to study the defects in FS and the connected pathways of charge carrier relaxation. First, we performed the optical characterization of the FS, including optical absorption, photoluminescence (PL) emission and excitation (PLE), and Fourier-transform infrared (FTIR) and Raman spectroscopy (RS). Based on the analysis of the PLE spectra and vibrational frequencies via RS and FTIR, we created a multi-transition Franck-Condon model, which is able to fully reproduce the PL and PLE spectra. Based on the experimental data and the Franck-Condon fit, we discuss two types of oxygen-deficient centres (ODC) present in this fused silica material and their emission pathways.